Analysis Of The Situation Of Malek Mosque In Kerman And The Necessity Of Restoration Of This Seljuq Building - Jamshid Roosta; Zohre Moqimizade (Journal of Universal History Studies, 2019)
The Seljuq government of Kerman (433-583 A.H. / 1042-1188 A.D.) is of the governments less studied and researched by Iranian researchers and scholars and this can be found in a small reflection on Persian studies on this dynasty. While the cultural and civil conditions of this governments and the elements existing in this culture convince the researcher to take a step, beyond a simple identification and expression of political history, to analyze and explain how these cultural elements entered and what the reasons were and how can the Seljuq architecture be exalted in Kerman. Undoubtedly, one of the main cultural and developmental symbols of the Seljuk government of Kerman is the Turānshah Mosque (the Malek Mosque). Therefore, in the present study, it is tried to firstly explain how the Seljuq government was formed in Kerman and at the second and most important stage, to explain how Malek Mosque was constructed and how its situation is. Therefore, the main questions are: how is the current situation of Malek Mosque? And how does new urbanism affect its physical space? The results of the present study shows that this mosque has been constructed in the Seljuq era and like other architectural monuments of the Seljuq era, it has a lot of strength and beauties. In spite of its many beauties, today, the building is less paid attention and needs to be maintained better and restoration of it seems essential.